This is GWAR [videorecording (DVD)] - Embry, Ethan, 1978-; Yankovic, Al, 1959-; Winter, Alex, 1965-; Lennon, Thomas, 1970- (Shudder, 2022)
The powerful story of the most iconic heavy metal/art collective/monster band in the universe, as told by the humans who have fought to keep it alive for over thirty years.